If it's not what You are looking for type in the equation solver your own equation and let us solve it.
b-9/6=-3
We move all terms to the left:
b-9/6-(-3)=0
We add all the numbers together, and all the variables
b+3-9/6=0
We multiply all the terms by the denominator
b*6-9+3*6=0
We add all the numbers together, and all the variables
b*6+9=0
Wy multiply elements
6b+9=0
We move all terms containing b to the left, all other terms to the right
6b=-9
b=-9/6
b=-1+1/2
| 12-3x+4x-3+5x=180 | | 8x-28+4x=20 | | 2v-7v=-33 | | 262=221-x | | 5x+2(x+4)=36 | | 5y+10=2y+7 | | 2(2x7)=18 | | A=7/5(h-42) | | c-(12-60)c=72 | | 7(8n+7)=329 | | −(9x−1.3)+8x=3(4x-7.8)3(4x−7.8) | | -9-r=1 | | t+(-4)32=t | | 2+p=1 | | 5(-6v-6)=28-v | | 2(x-5)-7=-17 | | 35=-5u=-48 | | 10+x=1/2(10x+4) | | -9x+18=15x | | 4(5x+9)=-18+14 | | x+11=3x+29 | | 8.5=6.5(d-30)+d | | 4(2x-8)=8x+33 | | (2a+21)=(3a-1) | | 8.5=6.5(2d-30+d | | 12x-13=7x+3 | | 13b+6=45 | | 5x-3(x+1)=2x+10 | | 8c+10-3=10c-5 | | 2x+26+2x+23=9 | | 3(-4y+9)=27 | | 8c+10−3c=10c−5 |